2021
DOI: 10.3389/fpsyt.2021.649494
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Transcriptional Profiling Highlights a Shift in Immune Signatures Over the Course of Illness in Schizophrenia

Abstract: With advanced understanding of the intricate interplay between the immune and central nervous systems in neurological and neuropsychiatric illness, there is renewed interest in the potential contribution of immune dysregulation to the development and progression of schizophrenia. To inform this line of inquiry requires a more nuanced understanding of specific immune changes throughout the course of illness. Here, we utilized a genome-wide sequencing approach to transcriptionally profile circulating monocytes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Microglial cells and chemokines might recruit monocytes circulating in the peripheral blood into the brain [ 38 ], where neuroinflammation was exacerbated by these monocytes. The investigation of monocyte transcriptome demonstrated a shift in monocyte phenotype in different stages of schizophrenia [ 39 ]. In the current study, the transcriptional profile of monocyte was directly related to the longitudinal change of cortical thickness in patients, suggesting an association of monocyte gene expression with the effect of treatment and this disease itself on the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial cells and chemokines might recruit monocytes circulating in the peripheral blood into the brain [ 38 ], where neuroinflammation was exacerbated by these monocytes. The investigation of monocyte transcriptome demonstrated a shift in monocyte phenotype in different stages of schizophrenia [ 39 ]. In the current study, the transcriptional profile of monocyte was directly related to the longitudinal change of cortical thickness in patients, suggesting an association of monocyte gene expression with the effect of treatment and this disease itself on the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between monocytosis and anosognosia is not new or limited to COVID-19, as it was reported earlier in the context of HIV-associated neurocognitive disorder (HAND), a condition marked by impaired insight [124]. This is significant as monocyte levels are elevated in SCZ, highlighting a potential general marker of anosognosia in neuropathology [125][126][127]. For example, a recent study found that patients in the preclinical phase of SCZ exhibited monocytosis and increased microbial translocation markers, further linking gut microbes with this pathology [128].…”
Section: Mononuclear Cells and Insightmentioning
confidence: 75%
“…Although no previous work has assessed gene expression profiles in monocytes from patients with OCD, some authors have described functional dysregulation of these immune cells in other psychiatric disorders based on gene expression changes. Thus, monocytes from patients with schizophrenia, bipolar disorder, or major depressive disorder showed abnormal gene expression patterns, with alterations in processes related to immune response, proinflammatory cytokine production, and cell adhesion/migration [ 38 41 ]. In addition, genome-wide expression studies using whole blood from those patients found impaired gene expression in some genes mostly related to monocytes and other cells of myeloid lineage [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%